2018
DOI: 10.1097/iae.0000000000001587
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Structural Alterations in the Choroid of Patients With Active Behçet Uveitis

Abstract: There was choroidal stromal expansion which was not associated with thickening of the choroid. Central foveal thickness may be used as a noninvasive measure to assess inflammatory activity in early Behçet uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 38 publications
2
29
1
1
Order By: Relevance
“…A decreased CVI was observed in other inflammatory disorders. A prospective study investigated choroidal alterations in patients with Behçet uveitis, reporting stromal expansion correlating with retinal vascular staining and leakage on fluorescein angiography [29].…”
Section: In Inflammatory Chorioretinal Disordersmentioning
confidence: 99%
“…A decreased CVI was observed in other inflammatory disorders. A prospective study investigated choroidal alterations in patients with Behçet uveitis, reporting stromal expansion correlating with retinal vascular staining and leakage on fluorescein angiography [29].…”
Section: In Inflammatory Chorioretinal Disordersmentioning
confidence: 99%
“…However, effacement replaces expansion as the disease progresses and chronic vascular injury settles [35][36][37][38]. Onal [39] et al reported choroidal stromal expansion without any association with ChT in patients with active Behçet's uveitis. It is noteworthy that in our series, none of the patients had an active uveitis or any other ocular involvement and only one patient had clinically active DADA2, suggesting that even under a successful treatment regimen, a mild subclinical inflammation may still exist.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] In contrast, a recent study in patients with Behçet's uveitis using the dual FA/ICGA scoring system showed that choroidal involvement (ICGA score) was insignificant and retinal involvement was highly preponderant over choroidal involvement in 100% (56/56) of the eyes. [ 13 ] This shows that FA/ICGA scoring is probably the best modality to date to evaluate and monitor posterior uveitis in practice and in clinical studies because it allows global and quantitative evaluation of inflammation in posterior uveitis.…”
Section: Discussionmentioning
confidence: 99%